EFFICACY OF DIETARY SUPPLEMENTATION OF AMBON BANANA MIDRIB SIMPLICIA TO ENHANCE GROWTH PERFORMANCE, HEMATOLOGICAL PROFILE, IMMUNITY, AND SURVIVAL OF CATFISH CHALLENGED WITH Edwardsiella tarda - Wahjuningrum, Dinamella; Nugroho, Riyanto; Yuhana, Munti; Citarasu, Thavasimuthu; Abdullah, Taufiq (Jurnal Riset Akuakultur, 2025)
Catfish (Clarias sp.) is a significant aquaculture species, but its production is often limited by Edwardsiella tarda infections, which cause substantial losses. Plant-derived alternatives such as banana midrib simplicia offer promising solutions to enhance fish health and reduce antibiotic dependence. This study investigated the effects of Ambon banana (Musa paradisiaca var. sapientum) midrib simplicia on growth performance, hematological parameters, immune responses, and resistance to E. tarda infection in catfish. A completely randomized design was used with five treatments and three replications, consisting of a positive control, a negative control, and commercial feed supplemented with 2% (B2), 3% (B3), and 4% (B4) banana midrib simplicia. The feeding trial lasted 30 days, after which fish were intramuscularly injected with E. tarda (10⁷ CFU mL⁻¹). Growth performance, hematological indicators (red blood cell count, hemoglobin concentration, hematocrit, and white blood cell count), immune responses (phagocytic and respiratory burst activities), and survival rate were evaluated. Dietary supplementation with banana midrib simplicia significantly improved growth performance, hematological parameters, immune responses, and survival in catfish challenged with E. tarda compared to the control groups. The optimal supplementation dose was 3%, providing the most significant improvement in growth, immunity, and survival. These findings highlight the potential of banana midrib as a functional feed additive derived from agricultural by-products to promote fish health and aquaculture productivity. Ikan lele (Clarias sp.) merupakan salah satu komoditas penting dalam akuakultur, namun produksinya sering terkendala oleh infeksi Edwardsiella tarda yang menyebabkan kerugian signifikan. Alternatif berbasis tanaman seperti simplisia pelepah pisang menawarkan solusi potensial untuk meningkatkan kesehatan ikan dan mengurangi ketergantungan terhadap antibiotik. Penelitian ini mengevaluasi pengaruh simplisia pelepah pisang Ambon (Musa paradisiaca var. sapientum) terhadap kinerja pertumbuhan, parameter hematologis, respons imun, dan ketahanan terhadap infeksi E. tarda pada ikan lele. Penelitian ini menggunakan rancangan acak lengkap dengan lima perlakuan dan tiga ulangan, terdiri atas kontrol positif, kontrol negatif, serta pakan komersial yang disuplementasi simplisia pelepah pisang pada dosis 2% (B2), 3% (B3), dan 4% (B4). Uji pemberian pakan dilakukan selama 30 hari, kemudian ikan diinjeksi intramuskular dengan E. tarda (10⁷ CFU mL⁻¹). Parameter yang diamati meliputi pertumbuhan, indikator hematologis (jumlah eritrosit, konsentrasi hemoglobin, hematokrit, dan jumlah leukosit), respons imun (aktivitas fagositosis dan respiratory burst), serta tingkat kelangsungan hidup. Suplementasi pakan dengan simplisia pelepah pisang secara signifikan meningkatkan performa pertumbuhan, parameter hematologis, respons imun, dan kelangsungan hidup ikan lele yang diinfeksi E. tarda dibanding kelompok kontrol. Dosis optimal diperoleh pada suplementasi 3%, yang memberikan peningkatan terbesar pada pertumbuhan, imunitas, dan kelangsungan hidup. Temuan ini menunjukkan bahwa simplisia pelepah pisang memiliki potensi sebagai aditif pakan fungsional berbasis limbah pertanian untuk meningkatkan kesehatan ikan dan produktivitas akuakultur.